The Knowledge of Sleep Medicine among Dental Interns in Northern Jordan - Alkhader, Mustafa; Saadeh, Rami (European Journal of Dentistry, 2020)
Objectives  The diagnosis and treatment of patients with sleep disorders are the most challenging issues in dentistry. The aim of this study was to assess the knowledge among dental interns in Northern Jordan about sleep medicine and sleep disorders.Materials and Methods This cross-sectional study was performed using the Assessment of Sleep Knowledge in Medical Education (ASKME) questionnaire. The questionnaire was given to 88 dental interns (52 females and 36 males) in Northern Jordan. Chi-squared test was utilized for data analysis.Results The mean score of the ASKME questionnaire was 12 out of 30 (40%). The majority of dental interns (88.6%) correctly answered ≤ 50% of the questions. No association was found between gender and score results.Conclusions Dental interns in Northern Jordan have a low level of knowledge about sleep medicine and sleep disorders. Dental faculties should provide courses related to sleep medicine throughout undergraduate education.
Keywords: sleep medicine knowledge; dental interns; ASKME questionnaire